PREVALENCE OF STROKE IN HAWLER, KURDISTAN REGION- IRAQ - Sheikhbzeni, Aso (Journal of Sulaimani Medical College, 2021)
Background Stroke is one of the significant health problems in Iraqi Kurdistan. No study addressing the prevalence of stroke has been conducted in this region. Objectives We aimed to find the prevalence of stroke in general in Hawler, the capital of Iraqi Kurdistan. Patients and Methods This cross-sectional study comprised a household survey of a clustered and randomly selected sample of the city’s population, and it was conducted from October 1st, 2018, to December 31st, 2019. Results Out of 4203 persons (905 families) we interviewed, only 33 patients (17 males and 16 females) had developed stroke, with a lifetime prevalence of 7.8/1000. Persons aged 60-74 years were the most typical target for stroke. The ratio of cerebral infarction (72.7%) to haemorrhage (27.3%) was 2.6:1. The subtypes of stroke were as follows: thrombotic 42.4%), embolic (12.1%), lacunar (18.2%), intracerebral haemorrhage (15.2%), and subarachnoid haemorrhage (12.1%). Hypertension was the most critical risk factor (54.5%), while smoking, diabetes mellitus, and hyperlipidemia were found to be other major risk factors. Conclusion Despite the lack of epidemiological data, the burden of stroke seems to be high in Hawler. Although ischemic strokes were more common than hemorrhagic ones, the relative proportion of haemorrhage was higher when compared to the Western population. There was no significant difference between genders in the disease pattern. Modifiable risk factors were common among patients with stroke.
Keywords: Stroke; cerebral infarction; Intracerebral haemorrhage; Subarachnoid haemorrhage; The prevalence